Analisis Proses Pengisian Jabatan Administrasi Berbasis Merit System di Kementerian Energi dan Sumber Daya Mineral - Riyan Afrianto; Eko Prasojo (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
After the issuance of Law No. 5 of 2014 concerning State Civil Apparatus, or better known as the ASN Law, the management of civil servants must be based on a merit system. Likewise with the process of filling structural positions, starting from the highest Main Leadership Position to the Supervisory Position must be based on merit systems. The position of High Leadership is explicitly stated in the ASN Law, it can be done through open bidding, while the level of Administrator and Supervisory positions is carried out with regard to the merit system. Even though it has been 4 years since the issuance of the ASN Law, there are not many central or regional agencies that have implemented the process of filling the Administrator and Supervisory Position on a merit system. The Ministry of Energy and Mineral Resources in the last 4 years, namely 2015-2018, has already carried out the process of mutation of positions 21 times, where the total number of officials who experienced mutations there were 1,775 people. Of the total 792 structural positions in the Ministry of Energy and Mineral Resources, there are 59 positions where the educational background of officials who occupy them is not in accordance with the competency of the positions they should have. The type of research used in this study is the type of analytical descriptive research through a qualitative approach. Source of data used in the form of primary data derived from in-depth interviews with research informants and secondary data in the form of archives and documentation. The informant selection technique uses purposive sampling. The results of the study found that the implementation of filling the Administrator Position and Supervisory Position at the Ministry of Energy and Mineral Resources in general was not entirely based on the principles of the merit system. There are still differences in procedures between Units in determining candidates for job selection, the absence of job competency standards causes measurement of participant competency can only be done in part, and the implementation of job rotation is not based on career patterns.